(untitled) (International Journal of Food and Nutritional Sciences, 2021)
Jackfruit peel synthesized by greener via blended with TiO2 nanoparticles. They verified with a variety of concentrations with & without coating of the distiller. Researchers fabricated the experimental setup analysis with the different parameters. Characterization results shows the functional energy additives; surface morphology; structure of chemicals. Its shows the potential values is 19.3 mV and crystalline is 85% 85% FTIR spectroscopy explains the bands of absorptions. Distillate yields of 4.96 L/m2 & 6.12 L/m2 efficiency achieved 102.64%.